2005
DOI: 10.1097/01.ede.0000158745.84019.c2
|View full text |Cite
|
Sign up to set email alerts
|

Parentʼs Age and the Risk of Oral Clefts

Abstract: Both high maternal age and high paternal age were associated with cleft lip with or without cleft palate. Higher paternal age but not maternal age increased the risk of cleft palate only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 28 publications
10
86
2
3
Order By: Relevance
“…Nonetheless, children of older fathers are not only more likely to have several diseases of clear genetic cause (Kühnert and Nieschlag, 2004;Lambert et al, 2006), they show also an increased risk for multifactorial diseases such as birth defects (Olshan et al, 1994;McIntosh et al, 1995;Kazaura et al, 2004;Bille et al, 2005;Zhu et al, 2005a, b;Archer et al, 2007;Yang et al, 2007), childhood cancers (Moll et al, 1996;Hemminki et al, 1999;Sharpe et al, 1999;Murray et al, 2002;Yip et al, 2006), prostate cancer (Zhang et al, 1999), breast cancer (controversial) (Colditz et al, 1991;Choi et al, 2005), diabetes mellitus type l (Bingley et al, 2000;Cardwell et al, 2005), multiple sclerosis (Montgomery et al, 2004), some forms of cerebral palsy (Fletcher and Foley, 1993), schizophrenia (Malaspina, 2001), bipolar disorder (Frans et al, 2008), autism (Reichenberg et al, 2006), epilepsy (Vestergaard et al, 2005), Alzheimer disease (Whalley et al, 1995) and lower intelligence quotients (Malaspina et al, 2005;Saha et al, 2009). However, some of the reported associations need to be considered with caution for methodological reasons in the statistical analysis, especially in regard to the validity of the data sources (Kirby, 2007) (Fig.…”
Section: Paternal Age and Outcome Of Offspringmentioning
confidence: 99%
“…Nonetheless, children of older fathers are not only more likely to have several diseases of clear genetic cause (Kühnert and Nieschlag, 2004;Lambert et al, 2006), they show also an increased risk for multifactorial diseases such as birth defects (Olshan et al, 1994;McIntosh et al, 1995;Kazaura et al, 2004;Bille et al, 2005;Zhu et al, 2005a, b;Archer et al, 2007;Yang et al, 2007), childhood cancers (Moll et al, 1996;Hemminki et al, 1999;Sharpe et al, 1999;Murray et al, 2002;Yip et al, 2006), prostate cancer (Zhang et al, 1999), breast cancer (controversial) (Colditz et al, 1991;Choi et al, 2005), diabetes mellitus type l (Bingley et al, 2000;Cardwell et al, 2005), multiple sclerosis (Montgomery et al, 2004), some forms of cerebral palsy (Fletcher and Foley, 1993), schizophrenia (Malaspina, 2001), bipolar disorder (Frans et al, 2008), autism (Reichenberg et al, 2006), epilepsy (Vestergaard et al, 2005), Alzheimer disease (Whalley et al, 1995) and lower intelligence quotients (Malaspina et al, 2005;Saha et al, 2009). However, some of the reported associations need to be considered with caution for methodological reasons in the statistical analysis, especially in regard to the validity of the data sources (Kirby, 2007) (Fig.…”
Section: Paternal Age and Outcome Of Offspringmentioning
confidence: 99%
“…31 A higher age of the mother is considered a risk factor for several chromosomal and non-chromosomal abnormalities; there is, however, no consensus as to whether maternal age is a risk factor for CLP. 33 In our sample only one father was aged 41 to 45 years ( Table 2). A study of 100 children with CLP revealed that maternal age was significant for the occurrence of clefts, and that ages 26 to 35 years and over 35 years had a lower risk for CLP compared to women aged up to 25 years.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have shown that older, rather than younger, mothers are more at risk of having children with cleft (e.g., Bille et al 2005). However, a higher risk among mothers under age 20 than among those aged 25-29 has been reported in the literature (Croen and Shaw 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The epidemiologic literature dealing with the effects of the ages of both parents on congenital anomalies more or less confirms these results. In one study (Bille et al 2005), both a high maternal age and a high paternal age were found to be associated with the occurrence of cleft lip with or without cleft palate, while a higher paternal age, but not a higher maternal age, was shown to increase the risk of having a child with cleft palate only. A Norwegian study confirmed the effect of the father's age, but not of the mother's age, on the incidence of cleft palate (Harville et al 2007).…”
Section: Introductionmentioning
confidence: 97%